KINETICS OF THE CASTING HARDENING AT VERTICAL CONTINUOUS CASTING WITH CLOSED LEVEL - E. I. Marukovich; E. B. Demchenko (Литьë и металлургия, 2006)
The kinetics of the casting hardening is studied at example of vertical moulding of solid cylindrical casting of cast iron with diameter 0,1 m.